DESIGN OF DATA PROCESSING SYSTEM CLAIMS ON ELECTRICITY AND WATER COOPERATION IN ANGKATAN LAUT RADIO DALAM - Dwi Dedy Hermawan; Yuce Yuliani, SKom, MM (Jurnal Sistem Informasi, 2000)
Having in mind the problems and constraints faced by the Cooperative Union Complex Gandaria (KOPERIA), it can find solutions to overcome these problems. By using a computerized data processing system will be very beneficial, and also to simplify the operational KOPERIA. Some of the benefits and advantages to be obtained KOPERIA among others: 1. Data and information needed can be presented soon. 2. The process of storing data (files) and reporting neatly. 3. Minimize the risk of lost data (files) in terms of manual processes. 4. Shorten the time and more efficient in processing information data. 5. Improving the quality of service (sevice) to members in particular and the surrounding communities KOPERIA cooperatives in general. In addition to the benefits and advantages of the above, there are many more beneficial use of computer facilities, particularly for data processing power and water bill that could be applied if KOPERIA.